INTEGRASI SEJARAH HUKUM KEMERDEKAAN INDONESIA DALAM PEMBELAJARAN IPS SEBAGAI UPAYA MENUMBUHKAN KESADARAN HUKUM SISWA SEKOLAH DASAR - Arief Rahman Sandi; Muhammad Saputra; Abd Thalib; Surizki Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines how the history of Indonesian independence law can be integrated into social studies teaching at elementary school level. Legal awareness among children in Indonesia tends to grow late, partly because historical and legal content in the curriculum is delivered as isolated facts rather than connected narratives. Using a qualitative descriptive approach supported by simple quantitative measurement, data were collected through classroom observation, document analysis of the social studies syllabus, interviews with grade V teachers, and a short comprehension test given before and after a one-semester teaching program at three elementary schools. Findings show that teachers rarely link independence-era legal milestones, such as the drafting of the 1945 Constitution and early nationality regulations, to present-day rights and obligations that pupils already experience. Three teaching patterns emerged among teachers who attempted integration: narrative retelling, contextual classroom discussion, and simple rule-making simulation. Pupils exposed to these patterns showed stronger comprehension gains on indicators of rights, obligations, and fairness compared with pupils taught through a conventional lecture-based approach. The study concludes that legal history offers a natural entry point for civic and legal literacy in elementary education, provided teachers are supported with contextual teaching materials, simple narrative techniques, and continued mentoring rather than isolated training sessions.